Nazi empire-building and the Holocaust in Ukraine - Lower, Wendy (University of North Carolina Press, 2005)
Creating Hitler's German colony in Ukraine On 16 July 1941, Adolf Hitler convened top Nazi leaders at his headquarters in East Prussia to dictate how they would rule the newly occupied eastern territories.